IL-17 and TNFα combination induces a HIF-1α-dependent invasive phenotype in synoviocytes. (22nd February 2012) - Zrioual, Saloua; Lenief, Vanina; Hot, Arnaud; Miossec, Pierre
Abstract : Objectives: To examine the effect of IL-17 on rheumatoid arthritis (RA) synoviocyte migration and invasiveness. Methods: IL-17A and tumour necrosis factor α (TNFα) induced mRNA expression in RA synoviocytes was analysed using Affymetrix U133A microarrays. The capacities of IL-17 alone or in combination with TNFα to induce synoviocyte migration and invasion were tested using Boyden and transwell Matrigel invasion chambers. A functional DNA binding assay was used to evaluate the regulation of the key hypoxia related gene HIF-1α expression and activation. The role of metalloproteinase 2 (MMP2) in IL-17 induced invasiveness was assessed using SiRNA. Hypoxia pathway gene expression was measured in blood of RA patients and healthy volunteers (HV) using Affymetrix microarrays. Results: Among the genes induced by IL-17A in RA synoviocytes, a molecular pattern of inflammation-hypoxia-related genes, including CXCR4 and MMP2 was identified. Using immunofluorence microscopy, the expression of CXCR4 on synoviocytes was confirmed. IL-17A and TNFα induced synoviocyte migration and invasion through a CXCR4-dependent mechanism with a synergistic effect. The combination of IL-17A and TNFα activated HIF1-α in synoviocytes through a NFκB pathway. IL-17 enhanced invasion through MMP2 induction as demonstrated using SiRNA. Finally, hypoxia genes were over expressed in the blood of RA patients. Conclusion: IL-17A, specifically when combined with TNFα may contribute to the progression of RA, notably through their effect on synoviocyte aggressiveness. Part of this effect results from CXCR4/SDF1 and hypoxia mediated pathways.